Bimbingan Teknis Pemanfaatan Limbah Kelapa Menjadi Arang Briket Di Desa Toari Kecamatan Toari Kabupaten Kolaka - Fitrianti Handayani; La Mpia; Mustafa R; Djunarlin Tojang; Maretik Maretik; Erfina Erfina; Sutrisnawati Mehora; La Ode Muhsafaat; Asni Asni (SEWAGATI: Jurnal Pengabdian Masyarakat Indonesia, 2024)
Toari Village is one of the villages in Toari District, Kolaka Regency. Toari Village has large, numerous and fertile coconut plantations. The majority of the people of Toari Village make their living as farmers. The main potential in the agricultural sector is coconut plants. With the large potential that can be developed and the low level of public knowledge in making charcoal briquettes, it is necessary to increase the skills of the community so that they are able to make it independently and sustainably so that after the activity ends, the community can utilize this knowledge and skills to make their own charcoal briquettes. This service will be implemented from October 2023 to December 2023. Implementation of activities in this service includes four stages, namely the preparation stage, counseling stage, training stage and evaluation stage. The conclusion from the results of this service is that the community is very enthusiastic in participating in this activity and the level of knowledge and skills of the community has increased.